An ANALYSIS OF SPEECH ACTS IN MOVIES : A LITERATURE REVIEW - Safira Ladita; Iwan Jazadi (STKIP Paracendekia NW Sumbawa, 2024)
A Speech acts are actions that occur simultaneously with utterances. This research aims to elucidate the current research landscape regarding the use of speech acts in several movies based on a literature review. The research approach employed is qualitative descriptive. Through a comprehensive literature review, the researcher applies a synthesis method to assess selected studies, culminating in the amalgamation of findings when comparisons allow. Ultimately, the study reveals that each examined movie contains various types of speech acts used by respective characters. However, some studies focus solely on one type of speech act.